THE SYNTHESIS OF THE NARRATOR AND THE ARTISTIC IMAGE AS AN AESTHETIC PRINCIPLE IN THE ESSAY (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
This article investigates how the fusion of narrator and artistic image functions as an aesthetic principle in the modern essay. Drawing on narrative theory, phenomenology, and stylistic analysis, the study demonstrates that this synthesis blurs the boundary between authorial self-expression and artistic representation. Through close reading of representative essays by Montaigne, Virginia Woolf, and Shukur Khollmirzaev, combined with insights from Bakhtinian dialogism and Genette’s focalization theory, the research reveals how the narrator’s subjectivity becomes an integral part of the artistic image itself. The findings highlight that such integration invites readers to experience the essay not merely as reportage or argument but as a lived aesthetic event.